New energy automobile electric cabinet copper bar stamping method

By precisely cutting the copper busbars of the electric control box of new energy vehicles, laser-cladding the surface with a silver-copper composite layer, and performing double protection treatment, the problems of increased resistance and charging current fluctuation during the copper busbar stamping process were solved, and the stability and reliability of the electrical performance were achieved.

CN120680251APending Publication Date: 2025-09-23KUNSHAN HUAKUI MACHINERY ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510958352.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

During the stamping process of the copper busbars in the electric control box of new energy vehicles, pits on the surface of the copper busbars, damage to the oxide layer or the gold plating layer will cause the resistance to increase, the charging current to fluctuate or even decrease, and form a functional defect of abnormal contact resistance.

Method used

The copper busbar is used for material pretreatment, through precision cutting and punching, drawing forming, surface laser cladding of silver-copper composite layer, tin plating instead of nickel plating, coating of PECVD nano coating and fluorosilicone sealing ring for double protection, deburring and using UV curing insulation coating.

Benefits of technology

It effectively reduces copper busbar wear, lowers contact resistance, improves conductivity and current carrying capacity, prevents abnormal contact resistance, and ensures the stability and reliability of electrical performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a new energy automobile electric cabinet copper bar stamping method which comprises the following steps: firstly, selecting a soft (T2M) or semi-hard (T2Y2) red copper bar with a rectangular or rounded rectangular cross section, carrying out acid pickling to remove an oxide layer, and polishing to improve the surface smoothness; and then the punching machine is used for being matched with the conveying chain plate to automatically clamp the copper bar, and high-precision cutting of the copper bar is achieved through the numerical control bending machine. After sharp burrs on the punched edge are ground and polished, the polished and worn part is coated with the PECVD nano coating to be matched with the fluorine silica gel sealing ring, so that double protection is achieved, direct wear to the copper bar is reduced, and meanwhile, a high-voltage wire is replaced with a UV curing insulating coating from a PET blue film to improve the voltage resistance value. And then the contact resistance and the current-carrying capacity of the copper bar are reduced by adopting a laser cladding silver-copper composite layer, and the conductivity of the copper bar is improved by replacing nickel plating with tin plating. Therefore, even if the resistance is increased due to a small part of abrasion caused by polishing, the contact resistance of the copper bar is not abnormal, so that the influence of functional defects is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of processing electric control boxes for new energy vehicles, and in particular to a method for stamping copper bars of electric control boxes for new energy vehicles. Background Art

[0002] Energy vehicles refer to vehicles that mainly or entirely use new clean energy as their power source. Their core features are different power sources, more environmentally friendly, and almost no tail gas emissions during use. The most common type of new energy vehicle is pure electric vehicles.

[0003] The electronic control box is the core intelligent control center of the high-voltage system of new energy vehicles, responsible for unified and coordinated management of the vehicle's energy flow, power output and high-voltage safety.

[0004] Because the electrical control box integrates key high-voltage ports such as the battery pack input, motor output, and charging interface, high current and power are generated during operation. Therefore, copper busbars, with their excellent conductivity and a cross-sectional area far exceeding that of cables, can carry these high currents with extremely low resistance loss, reducing energy waste and heat generation.

[0005] During the stamping process, copper busbars in current electrical control boxes are physically cut directly against the cutting tool. However, sharp burrs and linear scratches are easily formed at the edges. Left untreated, these burrs can easily pierce the insulation layer and cause short circuits. While existing technologies can eliminate these burrs through polishing, this process directly wears the copper busbar surface, causing pits on the surface and damage to the oxide layer or gold plating at the cut edges. This increases resistance, causes fluctuations or even a drop in charging current, and can easily lead to functional defects such as abnormal contact resistance. Summary of the Invention

[0006] The purpose of the present invention is to provide a method for stamping copper busbars for electric control boxes of new energy vehicles, which solves the functional defects of abnormal contact resistance caused by surface pits, damage to the oxide layer or gold plating layer during the copper busbar stamping process, resulting in increased resistance, fluctuation or even decrease in charging current.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for stamping copper bars of an electric control box of a new energy vehicle, comprising the following steps: Step 1: Material pretreatment: First, select a soft (T2M) or semi-hard (T2Y2) copper busbar with a rectangular or rounded rectangular cross-section, pickle it to remove the oxide layer, and then polish it to improve the surface finish; Step 2: Precision cutting and punching: Then use a punching machine with a transmission chain plate to automatically clamp the copper busbar, and use a CNC bending machine to achieve high-precision cutting of the copper busbar. Drill holes at the overlap according to the design specification tolerance. The hole diameter and position need to refer to the copper busbar width selection table to match the bolt size. Step 3: Drawing: The busbar is then processed using a bending machine or press brake. The bending angle must be precisely controlled to prevent cracking. Complex structures require multiple drawing steps. The flanging process enhances edge strength. Multiple layers of 0.5mm thin copper sheets are stacked and pressed into a soft busbar, and the ends are designed with anti-rotation structures. Step 4: Surface finishing: The silver-copper composite layer is then laser-clad onto the surface of the copper busbar, and the copper busbar is plated using a tin plating method using a methanesulfonic acid system instead of the traditional nickel plating process. The copper busbar is then passivated to resist sulfide corrosion. Step 5: Insulation reinforcement treatment: Use a polishing machine to remove burrs on the copper busbar's stamping edges, apply PECVD nano-coating on the stamping edges, and use fluorosilicone sealing rings to achieve double protection. At the same time, the high-voltage wires are replaced with UV-curable insulation coatings instead of PET blue film. Step 6: Quality inspection: Finally, the formed copper busbar is tested for appearance, dimensional tolerance, electrical performance, and mechanical performance according to conventional standards. The surface tin plating layer needs to be subjected to a 72-hour neutral salt spray test to ensure that the plating is uniform and without peeling.

[0008] Preferably, in step 1, the copper busbar has a resistivity of ≤0.01774Ω·mm² / m and a thickness tolerance of ±0.2mm. If insulation treatment is required, the busbar must be pre-wrapped with a PVC sleeve or treated with plastic dipping and have a flame retardant rating of V0.

[0009] Preferably, in step 2, the status of the punching machine fasteners, the lubrication system and the cleanliness of the mold are confirmed before operation to prevent faulty operation. The copper bar width / thickness tolerance is controlled within ±0.02mm, and a caliper is required for re-measurement before loading.

[0010] Preferably, in step 2, the punching burr height is ≤0.02mm to avoid scratching the insulating layer or causing tip discharge. The passivated tool needs to be automatically reciprocated by a grinding wheel to ensure a smooth incision. At the same time, the drill bit is matched according to the aperture in the drawing, and tapping is performed after the bottom hole is qualified to avoid thread deformation.

[0011] Preferably, in step 3, the bending process adopts step-by-step progressive forming (each bending ≤ 15°). After bending, the angle consistency needs to be checked to prevent stress concentration from causing cracks. At the same time, during the operation, personnel must wear insulating gloves, insulating shoes, use insulating tools, and keep a safe distance from the cutter.

[0012] Preferably, in step 4, the thickness of the silver-copper composite layer is 2-3 μm, and the contact resistance is ≤0.5 mΩ·cm²21; ultrasonic cleaning is used instead, and physical scratching of the coating is prohibited; the thickness of the tin plating layer is ≥3 μm.

[0013] Preferably, in step 5, the PECVD nanocoating thickness is less than 300nm, passes 10,000 friction tests, has a waterproof grade of IPX8, and has no VOC emissions. The fluorosilicone sealing ring has a temperature resistance range of -40°C to 200°C, and is combined with a phase change heat dissipation structure to achieve a temperature control accuracy of ±1°C.

[0014] Preferably, in step 6, the appearance and dimensional tolerance test requires visual inspection of the copper busbar surface, which must be free of burrs, cracks, oxidation spots or deformation. A caliper is used to measure the length / width / thickness, and the tolerance must meet the requirements of the design drawing. At the same time, the orange PVC / TPE insulation layer must not be damaged.

[0015] Preferably, in step 6, the electrical performance test requires measuring the voltage drop △U=U-U1 across the contact at a set current (such as 400A) and comparing the output voltage, which is required to meet technical specifications; under DC 1000V conditions, the insulation resistance is ≥500MΩ; the charging socket insulation resistance (AC) is ≥1MΩ613; the resistivity is ≤0.018Ω·mm² / m (20°C), and the conductivity is ≥98%IACS.

[0016] Preferably, in step 6, the mechanical performance test requires 10-1000Hz random vibration, RMS 27.8m / s², the copper busbar is not broken or loose, and 5g acceleration and 15ms half-sine wave shock are performed to verify the deformation resistance of the installation point, and then a wide side 90° bending test is performed to ensure that there are no cracks on the surface.

[0017] Compared with the prior art, the present invention has the following beneficial effects: This patented method achieves dual protection by polishing sharp burrs on the punched edges and then applying a PECVD nano-coating and a fluorosilicone sealing ring to the polished areas, reducing direct wear on the copper busbar. Simultaneously, the high-voltage conductors are replaced with a UV-curable insulation coating instead of a PET blue film to improve the withstand voltage. Laser cladding of a silver-copper composite layer is then used to reduce the contact resistance and current carrying capacity of the copper busbar, while tin plating replaces nickel plating to improve its conductivity. This ensures that even if a small amount of wear increases resistance due to polishing, it will not cause abnormal contact resistance of the copper busbar, thereby preventing functional defects. DETAILED DESCRIPTION

[0018] The present invention will be described in more detail below by way of examples. These examples are merely illustrative and do not limit the scope of the present invention in any way.

[0019] The present invention provides a technical solution: a method for stamping copper bars of an electric control box of a new energy vehicle, comprising the following steps: Step 1: Material pretreatment: First, select a soft (T2M) or semi-hard (T2Y2) copper busbar with a rectangular or rounded rectangular cross-section, pickle it to remove the oxide layer, and then polish it to improve the surface finish; Step 2: Precision cutting and punching: Then use a punching machine with a transmission chain plate to automatically clamp the copper busbar, and use a CNC bending machine to achieve high-precision cutting of the copper busbar. Drill holes at the overlap according to the design specification tolerance. The hole diameter and position need to refer to the copper busbar width selection table to match the bolt size. Step 3: Drawing: The busbar is then processed using a bending machine or press brake. The bending angle must be precisely controlled to prevent cracking. Complex structures require multiple drawing steps. The flanging process enhances edge strength. Multiple layers of 0.5mm thin copper sheets are stacked and pressed into a soft busbar, and the ends are designed with anti-rotation structures. Step 4: Surface finishing: The silver-copper composite layer is then laser-clad onto the surface of the copper busbar, and the copper busbar is plated using a tin plating method using a methanesulfonic acid system instead of the traditional nickel plating process. The copper busbar is then passivated to resist sulfide corrosion. Step 5: Insulation reinforcement treatment: Use a polishing machine to remove burrs on the copper busbar's stamping edges, apply PECVD nano-coating on the stamping edges, and use fluorosilicone sealing rings to achieve double protection. At the same time, the high-voltage wires are replaced with UV-curable insulation coatings instead of PET blue film. Step 6: Quality inspection: Finally, the formed copper busbar is tested for appearance, dimensional tolerance, electrical performance, and mechanical performance according to conventional standards. The surface tin plating layer needs to be subjected to a 72-hour neutral salt spray test to ensure that the plating is uniform and without peeling.

[0020] Example 1: First, select soft (T2M) or semi-hard (T2Y2) copper busbars with rectangular or rounded rectangular cross-sections, pickle them to remove the oxide layer, and polish them to improve the surface finish. Then, use a stamping machine with a transmission chain to automatically clamp the copper busbar, and use a CNC bending machine to achieve high-precision cutting of the copper busbar. Drill holes at the overlap according to the design specification tolerance. The hole diameter and position should refer to the copper busbar width selection table to match the bolt size. Then use a bending machine or a bending machine for processing. The bending angle must be precisely controlled to avoid cracking of the copper busbar. Complex structures require multi-step drawing and forming. The flanging process enhances edge strength. Multiple layers of 0.5mm thin copper sheets are stacked and pressed into a soft busbar, and the ends are protected. Convert the structural design; then the silver-copper composite layer is laser clad onto the surface of the copper busbar, and the copper busbar is plated with tin plating using a methanesulfonic acid system instead of the traditional nickel plating process, and then the copper busbar surface is passivated to resist sulfide corrosion; a polishing machine is used to remove burrs on the stamping edge of the copper busbar, and a PECVD nano-coating is applied on the stamping edge, and a fluorosilicone sealing ring is used to achieve double protection. At the same time, the high-voltage wire is replaced with a UV-cured insulating coating from a PET blue film; finally, the formed copper busbar is tested for appearance, dimensional tolerance, electrical performance, and mechanical performance according to conventional standards. The surface tin plating layer needs to be subjected to a 72-hour neutral salt spray test to ensure that the coating is uniform and not peeling.

[0021] Example 2: In Example 1, the following steps are added: In step 1, the copper busbar must have a resistivity of ≤0.01774Ω·mm² / m and a thickness tolerance of ±0.2mm. If insulation is required, it must be pre-wrapped with PVC tubing or treated with plastic dipping, and its flame retardancy must meet V0.

[0022] In step 2, before operation, the status of the punching machine's fasteners, lubrication system, and mold cleanliness are confirmed to prevent faulty operation. The copper bar width / thickness tolerance is controlled at ±0.02mm, and a caliper is required for re-measurement before loading. The punching burr height is ≤0.02mm to avoid scratching the insulation layer or causing tip discharge. The passivated tool needs to be automatically reciprocated with a grinding wheel to ensure a smooth incision. At the same time, the drill bit is matched to the aperture on the drawing, and tapping is performed only after the bottom hole is qualified to avoid thread deformation.

[0023] First, select soft (T2M) or semi-rigid (T2Y2) copper busbars with rectangular or rounded rectangular cross-sections. They are pickled to remove the oxide layer and then polished to improve the surface finish. The copper busbars must have a resistivity of ≤0.01774Ω·mm² / m and a thickness tolerance of ±0.2mm. If insulation is required, they must be pre-coated with PVC tubing or treated with plastic dipping, and must meet V0 flame retardancy. The copper busbar is then automatically clamped using a stamping machine in conjunction with a transmission chain plate, and high-precision cutting of the copper busbar is achieved using a CNC bending machine. Holes are drilled at the overlap according to the design specification tolerance. The hole diameter and position must be matched to the bolt size based on the copper busbar width selection table. Before operation, the status of the stamping machine's fasteners, lubrication system, and mold cleanliness must be confirmed to prevent faulty operation. The copper busbar material width / thickness tolerance is controlled within ±0.02mm, and caliper re-measurement is required before loading. The stamping burr height is ≤0.02mm to avoid scratching the insulation layer or causing tip discharge. The passivated tool must be automatically reciprocated with a grinding wheel to ensure a smooth cut. At the same time, the drill bit is matched to the hole diameter on the drawing. Tapping is performed only after the bottom hole is qualified to avoid thread deformation. The busbar is then processed using a bending or press brake, with the bending angle precisely controlled to prevent cracking. Complex structures require multiple drawing steps, with flanging enhancing edge strength. Multiple layers of 0.5mm thin copper sheets are stacked and pressed into a soft busbar, with anti-rotation features designed into the ends. A silver-copper composite layer is then laser-clad onto the surface of the busbar, and the traditional nickel plating process is used to coat the copper busbar using a methylsulfonic acid-based tin plating method. The surface is then passivated to resist sulfide corrosion. A polishing machine is then used to remove burrs from the stamped edges of the copper busbar, and a PECVD nano-coating is applied to the stamped edges. A fluorosilicone sealing ring is used for double protection, and the high-voltage conductors are replaced with a UV-curable insulation coating instead of a PET blue film. Finally, the formed copper busbar is tested for appearance, dimensional tolerance, electrical performance, and mechanical properties according to conventional standards. The surface tin plating is subjected to a 72-hour neutral salt spray test to ensure that the coating is uniform and free of peeling.

[0024] Example 3: In Example 2, the following steps are added: In step 3, the bending process adopts step-by-step progressive forming (each bend ≤15°). After bending, the angle consistency needs to be checked to prevent stress concentration from causing cracks. During the operation, personnel must wear insulating gloves and insulating shoes, use insulating tools, and keep a safe distance from the cutter.

[0025] In step 4, the thickness of the silver-copper composite layer is 2-3 μm, and the contact resistance is ≤0.5 mΩ·cm²21; ultrasonic cleaning is used instead, and physical scratching of the coating is prohibited; the thickness of the tin plating layer is ≥3 μm.

[0026] First, select soft (T2M) or semi-rigid (T2Y2) copper busbars with rectangular or rounded rectangular cross-sections. They are pickled to remove the oxide layer and then polished to improve the surface finish. The copper busbars must have a resistivity of ≤0.01774Ω·mm² / m and a thickness tolerance of ±0.2mm. If insulation is required, they must be pre-coated with PVC tubing or treated with plastic dipping, and must meet V0 flame retardancy. The copper busbar is then automatically clamped using a stamping machine in conjunction with a transmission chain plate, and high-precision cutting of the copper busbar is achieved using a CNC bending machine. Holes are drilled at the overlap according to the design specification tolerance. The hole diameter and position must be matched to the bolt size based on the copper busbar width selection table. Before operation, the status of the stamping machine's fasteners, lubrication system, and mold cleanliness must be confirmed to prevent faulty operation. The copper busbar material width / thickness tolerance is controlled within ±0.02mm, and caliper re-measurement is required before loading. The stamping burr height is ≤0.02mm to avoid scratching the insulation layer or causing tip discharge. The passivated tool must be automatically reciprocated with a grinding wheel to ensure a smooth cut. At the same time, the drill bit is matched to the hole diameter on the drawing. Tapping is performed only after the bottom hole is qualified to avoid thread deformation. The busbars are then processed using a bending or press brake. The bending angle must be precisely controlled to prevent cracking. Complex structures require multiple drawing steps, with flanging to enhance edge strength. Multiple layers of 0.5mm thin copper sheets are laminated and pressed into a flexible busbar, with anti-rotation features designed into the ends. The bending process is a step-by-step, incremental process (each bend ≤15°). After bending, the angle consistency must be checked to prevent stress concentration and cracking. During operation, personnel must wear insulating gloves and shoes, use insulating tools, and maintain a safe distance from cutting tools. A silver-copper composite layer is then laser-clad onto the copper busbar surface. Tin plating with a methanesulfonic acid system replaces the traditional nickel plating process. The copper busbar surface is then passivated to resist sulfidation corrosion. The silver-copper composite layer is 2-3μm thick, with a contact resistance of ≤0.5mΩ·cm²21. Ultrasonic cleaning is used instead, and physical scratching of the coating is prohibited. The tin plating thickness is ≥3μm. A polishing machine is then used to remove burrs from the stamping edges of the copper busbars, and a PECVD nano-coating is applied to the stamping edges, combined with a fluorosilicone sealing ring for double protection. At the same time, the high-voltage conductors are replaced with UV-cured insulating coatings from PET blue film. Finally, the formed copper busbars are tested for appearance, dimensional tolerance, electrical properties, and mechanical properties according to conventional standards. The surface tin plating layer is subjected to a 72-hour neutral salt spray test to ensure that the plating is uniform and free of peeling.

[0027] Example 4: In Example 3, the following steps are added: In step 5, the PECVD nano-coating thickness is less than 300nm, passes 10,000 friction tests, has a waterproof rating of IPX8, and has no VOC emissions. The fluorosilicone sealing ring has a temperature resistance range of -40°C to 200°C, and is combined with a phase change heat dissipation structure to achieve a temperature control accuracy of ±1°C.

[0028] In step 6, the appearance and dimensional tolerance tests require a visual inspection of the copper busbar surface. The surface must be free of burrs, cracks, oxidation spots, or deformation. Calipers should be used to measure the length, width, and thickness. The tolerances must meet the design drawing requirements, and the orange PVC / TPE insulation layer must be intact. The electrical performance test requires measuring the voltage drop (△U = U - U1) across the contacts at a set current (e.g., 400A). The output voltage must be compared and meet technical specifications. At 1000V DC, the insulation resistance must be ≥500MΩ. The insulation resistance (AC) of the charging socket must be ≥1MΩ613. The resistivity must be ≤0.018Ω·mm² / m (at 20°C), and the conductivity must be ≥98% IACS. The mechanical performance test requires random vibration testing at 10-1000Hz, RMS 27.8m / s², to ensure the copper busbar is free of breakage or looseness. A 5g acceleration and 15ms half-sine shock test is also performed to verify the deformation resistance of the mounting point. A 90° wide-side bend test is then performed to ensure the surface is free of cracks.

[0029] First, select soft (T2M) or semi-rigid (T2Y2) copper busbars with rectangular or rounded rectangular cross-sections. They are pickled to remove the oxide layer and then polished to improve the surface finish. The copper busbars must have a resistivity of ≤0.01774Ω·mm² / m and a thickness tolerance of ±0.2mm. If insulation is required, they must be pre-coated with PVC tubing or treated with plastic dipping, and must meet V0 flame retardancy. The copper busbar is then automatically clamped using a stamping machine in conjunction with a transmission chain plate, and high-precision cutting of the copper busbar is achieved using a CNC bending machine. Holes are drilled at the overlap according to the design specification tolerance. The hole diameter and position must be matched to the bolt size based on the copper busbar width selection table. Before operation, the status of the stamping machine's fasteners, lubrication system, and mold cleanliness must be confirmed to prevent faulty operation. The copper busbar material width / thickness tolerance is controlled within ±0.02mm, and caliper re-measurement is required before loading. The stamping burr height is ≤0.02mm to avoid scratching the insulation layer or causing tip discharge. The passivated tool must be automatically reciprocated with a grinding wheel to ensure a smooth cut. At the same time, the drill bit is matched to the hole diameter on the drawing. Tapping is performed only after the bottom hole is qualified to avoid thread deformation. The busbars are then processed using a bending or press brake. The bending angle must be precisely controlled to prevent cracking. Complex structures require multiple drawing steps, with flanging to enhance edge strength. Multiple layers of 0.5mm thin copper sheets are laminated and pressed into a flexible busbar, with anti-rotation features designed into the ends. The bending process is a step-by-step, incremental process (each bend ≤15°). After bending, the angle consistency must be checked to prevent stress concentration and cracking. During operation, personnel must wear insulating gloves and shoes, use insulating tools, and maintain a safe distance from cutting tools. A silver-copper composite layer is then laser-clad onto the copper busbar surface. Tin plating with a methanesulfonic acid system replaces the traditional nickel plating process. The copper busbar surface is then passivated to resist sulfidation corrosion. The silver-copper composite layer is 2-3μm thick, with a contact resistance of ≤0.5mΩ·cm²21. Ultrasonic cleaning is used instead, and physical scratching of the coating is prohibited. The tin plating thickness is ≥3μm. A polishing machine is then used to remove burrs from the stamping edges of the copper busbar, and a PECVD nano-coating is applied to the stamping edges, combined with a fluorosilicone sealing ring to achieve double protection. At the same time, the high-voltage wires are replaced with a UV-cured insulating coating from a PET blue film. The PECVD nano-coating is less than 300nm thick and has passed 10,000 friction tests, with an IPX8 waterproof rating and no VOC emissions. The fluorosilicone sealing ring has a temperature resistance range of -40°C to 200°C, and is combined with a phase change heat dissipation structure to achieve a temperature control accuracy of ±1°C.Finally, the formed copper busbar is tested for appearance, dimensional tolerance, electrical performance, and mechanical performance according to conventional standards. The surface tin plating layer needs to be subjected to a 72-hour neutral salt spray test to ensure that the plating is uniform and without peeling. The copper busbar surface needs to be visually inspected for burrs, cracks, oxidation spots, or deformation during the appearance and dimensional tolerance tests. The length / width / thickness should be measured with a caliper. The tolerance should meet the requirements of the design drawings. The orange PVC / TPE insulation layer should be intact. The electrical performance test requires measuring the voltage drop △U=U-U1 across the contact at a set current (such as 400A) and comparing the output voltage. The test is required to meet the technical specifications. Under DC 1000V conditions, the insulation resistance is ≥500MΩ; the charging socket insulation resistance (AC) is ≥1MΩ613; the resistivity is ≤0.018Ω·mm² / m (20℃), and the conductivity is ≥98%IACS. The mechanical performance test requires 10-1000Hz random vibration, RMS 27.8m / s², the copper busbar is not broken or loose, and 5g acceleration and 15ms half-sine wave shock are applied to verify the deformation resistance of the installation point. Then a 90° wide-side bending test is performed, and no cracks are found on the surface.

[0030] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A method for stamping copper bars for electric control boxes of new energy vehicles, characterized by: The following steps are involved: Step 1: Material pretreatment: First, select a soft (T2M) or semi-hard (T2Y2) copper busbar with a rectangular or rounded rectangular cross-section, pickle it to remove the oxide layer, and then polish it to improve the surface finish; Step 2: Precision cutting and punching: Then use a punching machine with a transmission chain plate to automatically clamp the copper busbar, and use a CNC bending machine to achieve high-precision cutting of the copper busbar. Drill holes at the overlap according to the design specification tolerance. The hole diameter and position need to refer to the copper busbar width selection table to match the bolt size. Step 3: Drawing: The busbar is then processed using a bending machine or press brake. The bending angle must be precisely controlled to prevent cracking. Complex structures require multiple drawing steps. The flanging process enhances edge strength. Multiple layers of 0.5mm thin copper sheets are stacked and pressed into a soft busbar, and the ends are designed with anti-rotation structures. Step 4: Surface finishing: The silver-copper composite layer is then laser-clad onto the surface of the copper busbar, and the copper busbar is plated using a tin plating method using a methanesulfonic acid system instead of the traditional nickel plating process. The copper busbar is then passivated to resist sulfide corrosion. Step 5: Insulation reinforcement treatment: Use a polishing machine to remove burrs on the copper busbar's stamping edges, apply PECVD nano-coating on the stamping edges, and use fluorosilicone sealing rings to achieve double protection. At the same time, the high-voltage wires are replaced with UV-curable insulation coatings instead of PET blue film. Step 6: Quality Inspection: Finally, the formed copper busbar is tested for appearance, dimensional tolerance, electrical performance, and mechanical performance according to conventional standards. The surface tin plating layer needs to be subjected to a 72-hour neutral salt spray test to ensure that the plating is uniform and without peeling.

2. A copper busbar stamping method for an electric control box of a new energy vehicle according to claim 1, characterized in that: In step 1, the copper busbar is required to have a resistivity of ≤0.01774Ω·mm² / m and a thickness tolerance of ±0.2mm. When insulation treatment is required, it must be pre-wrapped with PVC sleeve or plastic-dip treated and the flame retardant grade must reach V0 level.

3. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 2, the status of the press fasteners, lubrication system, and mold cleanliness are confirmed before operation to prevent faulty operation. The width / thickness tolerance of the copper bar is controlled within ±0.02mm, and a caliper is required for re-measurement before loading.

4. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 2, the punching burr height is ≤0.02mm to avoid scratching the insulation layer or causing tip discharge. The passivated tool needs to be automatically reciprocated by a grinding wheel to ensure a smooth cut. At the same time, the drill bit is matched according to the aperture of the drawing. After the bottom hole is qualified, tapping is performed to avoid thread deformation.

5. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 3, the bending process adopts step-by-step progressive forming (each bend ≤ 15°). After bending, the angle consistency needs to be checked to prevent stress concentration from causing cracks. During the operation, personnel must wear insulating gloves and insulating shoes, use insulating tools, and keep a safe distance from the cutter.

6. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 4, the thickness of the silver-copper composite layer is 2-3 μm, and the contact resistance is ≤0.5 mΩ·cm²21; ultrasonic cleaning is used instead, and physical scratching of the coating is prohibited; the thickness of the tin plating layer is ≥3 μm.

7. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 5, the PECVD nano-coating thickness is less than 300nm, passes 10,000 friction tests, has a waterproof grade of IPX8, and has no VOC emissions. The fluorosilicone sealing ring has a temperature resistance range of -40°C to 200°C, and is combined with a phase change heat dissipation structure to achieve a temperature control accuracy of ±1°C.

8. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 6, the appearance and dimensional tolerance test requires visual inspection of the copper busbar surface. It is required to be free of burrs, cracks, oxidation spots or deformation. The length / width / thickness is measured with a caliper. The tolerance must meet the requirements of the design drawing. At the same time, the orange PVC / TPE insulation layer must be intact.

9. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 6, the electrical performance test requires measuring the voltage drop across the contacts (△U = U - U1) at a set current (e.g., 400A) and comparing the output voltages. This test must meet technical specifications. At 1000V DC, the insulation resistance must be ≥500MΩ; the charging socket insulation resistance (AC) must be ≥1MΩ613; the resistivity must be ≤0.018Ω·mm² / m (20°C); and the conductivity must be ≥98% IACS.

10. The method for punching copper bars of electric control boxes for new energy vehicles according to claim 1, characterized in that: In step 6, the mechanical performance test requires 10-1000Hz random vibration, RMS 27.8m / s², to ensure that the copper busbar is not broken or loose. 5g acceleration and 15ms half-sine wave shock are also applied to verify the deformation resistance of the installation point. Then, a 90° wide-side bend test is performed to ensure that there are no cracks on the surface.